Estrutura de governo e ação política feminista: a experiência do PT na Prefeitura de São Paulo - Delgado, Maria do Carmo Godinho (2007)
The present study focuses on the creation of governmental mechanisms, arisen in Brazil as of the 1980s, designed to guide government intervention in women-related policies. It analyzes the proposal, drafted by Workers Party feminist militants, of a government body for elaboration, formulation and policy-executing, in conjunction with other government areas, so as to propel the implementation of government political action from a feminist perspective. It places the drafting of the proposal within the framework of the emergence of women as a new political and social actor in the country, who organized a strong movement in the late years of the dictatorship and pointed to the need for building specific instruments to influence State action; hence, the creation of the councils on the status of women, as mediating bodies between the women s movement and the State; a model distinct from that advocated by other Workers Party feminists. Considering the critique presented by the Workers Party feminists regarding the ambiguity present in the concept underlying the councils on the status of women, the thesis analyzes the implementation of the Workers Party proposal at the two moments during which the party took over the local government of the city of São Paulo (1989-1992 and 2001-2004), with the creation of the Women s Special Coordination (Coordenadoria Especial da Mulher). It points out constraints to the proposal s assimilation by the party and the potentialities of feminist action within the administration, boosted by a government structure designed to that end. It confirms that the hierarchical locus in the government s organizational structure and the legitimacy and authority for this body s mandate tributaries of the weight that the nucleus of the government attributes to it are crucial for its action to be efficacious, affecting also conditions available for performing the task. It argues that the women s movement is a central actor in pushing for changes in State action, albeit not sufficient. The presence of a feminist core inside political parties is decisive for the State to adopt policies in favor of women, given that parties are the central agents in forming governments. It also indicates that the political and economic context and the strategic choices made by the women s movement strongly influence the likelihood of the State including women policies in its agenda. It considers that State action is still guided by a limited concept of women s citizenship, which ascribes to them the priority responsibility for social reproduction, founded on the dichotomy between public and private. It draws on elaborations on social relations of sex and on the sexual division of labour as theoretical instruments that would better explain the dynamic of inequality between women and men, to the detriment of the form whereby the concept of gender was overwhelmingly incorporated in Brazil